The Livestock Sector in TRNC: An Examination of Red Meat Sector - Esendağlı, İrfan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
In today's changing and developing world, one of the most important problems that people face is a balanced diet. To continue their lives in a healthy way, people should consume animal source foods in sufficient quantities. Although the share of the agriculture sector in the TRNC economy has decreased from the past to the present, it always has a place that cannot be neglected in the economy due to its importance in the diet of individuals because meeting the basic needs of individuals in their daily life sufficiently is one of the main duties of the agriculture sector. In addition to its importance in human nutrition, red meat also contributes greatly to the economies of countries due to the employment of many people and its contribution to national development. In the TRNC, the red meat sector is important for the economy as it creates both consumption and a large employment area. In addition to all these advantages, the fact that red meat and its products have a significant share in local flavors makes the red meat sector important for the TRNC economy. Since the TRNC does not have a liberal economy, there is no large scale import in this sector. However, recently, the thinking of red meat imports and the decision to import led to further discussion of the problems experienced in red meat production and the factors affecting production. The decision to import red meat supports the depth of existing problems in this field today. This study reveals the necessity of policies that will bring structural solutions in order to overcome the problems encountered as a result of the analyzes covering the TRNC red meat sector. In other words, the aim of the study is to reveal the current situation and problems of the red meat sector and to provide suggestions for solutions. In this way, it is aimed to minimize the problems in the sector and eliminate the negative effects on both the sector and economic development. In the case of TRNC, there has been no previous study on this subject in such detail, so it constitutes a precedent.

ÖZ: Günümüzde değişen ve gelişen dünyada, insanların karşılaştıkları en önemli sorunlarından biri de dengeli beslenmedir. Bireylerin yaşamlarını sağlıklı bir şekilde devam ettirebilmeleri için hayvansal kaynaklı gıdaları yeterli miktarlarda tüketmeleri gerekmektedir. Bireylerin gündelik hayattaki temel ihtiyaçlarının yeterli ve nitelikli olarak karşılanmasının tarım sektörünün temel görevlerinden birisi olması nedeniyle, her ne kadar geçmişten günümüze değin tarım sektörünün KKTC ekonomisi içerisindeki payı azalmış olsa dahi, bireylerin beslenmesindeki önemi gereği her zaman ekonomi içinde ihmal edilemeyecek bir yeri bulunmaktadır. Kırmızı et, insan beslenmesindeki öneminin yanı sıra, birçok kişiye istihdam sağlaması ve ulusal kalkınmaya olan katkısı nedeniyle ülkelerin ekonomilerine de büyük katkı da bulunmaktadır. KKTC’de hem tüketim, hem de geniş bir istihdam alanı yaratması nedeniyle kırmızı et sektörü KKTC ekonomisi için hayati bir öneme sahiptir. Bir diğer ifadeyle, kırmızı et sektörü gerek beslenmedeki yeri gerekse üretimdeki mevcut potansiyeli nedeniyle KKTC için kritik öneme sahiptir. Tüm bu avantajlara ek olarak, yerel lezzetlerinde kırmızı et ve ürünlerinin önemli bir paya sahip olması kırmızı et sektörünü KKTC ekonomisi için önemli kılmaktadır. KKTC liberal bir ekonomiye sahip olmadığı için bu sektörde geniş çaplı ithalat yapılmamaktadır. Fakat, son dönemlerde kırmızı et ithalatının gündeme gelmesi ve ithalat kararının alınması, kırmızı et üretiminde yaşanan sorunları ve üretimi etkileyen faktörlerin kamuoyunda daha fazla tartışılmasına yol açmıştır. Kırmızı et ithalatı kararının alınması günümüzde bu alanda varolan sorunların derinliğini destekler niteliktedir. Bu çalışma KKTC kırmızı et sektörünü kapsayan analizler sonucunda karşılaşılan sorunların giderilebilmesi için yapısal çözümler getirecek politikaların gerekliliğini ortaya koymaktadır. Bir diğer ifadeyle, çalışmanın amacı kırmızı et sektörünün mevcut durumunun ve sorunlarının ortaya konulmasını ve çözüm önerilerinin getirilmesini sağlamaktır. Böylelikle, sektördeki sorunları en aza indirerek hem sektördeki hem de ekonomik gelişme üzerindeki olumsuz etkilerin giderilmesi amaçlanmaktadır. KKTC özelinde, daha önce bu konu hakkında bu kadar detaylı bir şekilde yapılmış herhangi bir çalışma bulunmamaktadır. Bu nedenle emsal teşkil etmektedir.
Master of Science in Economics. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2021. Supervisor: Assoc. Prof. Dr. Kamil Sertoğlu.
Keywords: Economics Department; Economic Conditions and Development--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Livestock Sector--Red Meat Sector--Cyprus (Turkish Republic of Northern Cyprus, 1983-); Livestock--Economic aspects; Animal industry; Animal Source Food, Red Meat, TRNC, Livestock Sector, Problems, Solutions